Impact of a 12-week supervised exercise program on weight loss trajectory, daily physical activity levels and sedentary behaviors after bariatric surgery. (14th October 2021) - Lemieux-Simard, C; Pettigrew, M; Auclair, A; Piche, M E; Biertho, L; Marceau, S; Harvey, J; Poirier, P
Abstract: Background: The evidence suggests that physical activity (PA) following bariatric surgery can enhance weight loss and other metabolic outcomes. However, most individuals with severe obesity are insufficiently active, and without support, fail to make substantial increases in their daily PA levels postoperatively. Purpose: The aim of this study was to investigate the effectiveness of a 12-week supervised exercise program on daily PA levels, sedentary time, and on maintenance of the weight loss trajectory following bariatric surgery. Methods: Fifty-nine individuals with severe obesity (body mass index [BMI] ≥40 or ≥35 kg/m 2 with comorbidities) eligible for bariatric surgery were randomly assigned (1:2) to either standard of care (CG, n=19) or a 12-week supervised exercise program (ExG, n=40). Daily PA levels and sedentary time were assessed using an armband accelerometer worn over a 3-day period (2 week-day and 1 weekend day). Body weight, body fat and fat-free mass were assessed using bioelectrical impedance balance. The exercise training program (60 min, 3 times per week for 12 weeks) started 3 months after the bariatric surgery and was supervised by a certified clinical exercise physiologist. Daily PA levels, sedentary time and anthropometric measurements were obtained preoperatively, and at 3, 6 and 12 months after bariatric surgery. Results: Age of participants was 42±12 years, BMI was 46±6 kg/m 2, and 76% were women. Before the exercise training program, PA parameters (daily PA levels, sedentary time and moderate to vigorous intensity PA [MVPA] were comparable between groups. Following the exercise training program, the ExG showed a significant reduction in sedentary time (753±113 to 721±88 min/day), an increase in daily PA levels (4544±1863 to 5853±3101 steps/day) and in MVPA levels (18.8±25.1 to 30.5±38.1 min/day). Further increase in daily MVPA levels were observed at the 12 months follow-up visit (p=0.05). In the standard of care group, changes in PA parameters were also comparable to those in the ExG. All anthropometric measurements indicate statistically significant changes postoperatively, after the intervention and up to 12 months follow-up (p<0.001) without showing any difference between groups. Anthropometric changes up to 12 months follow-up show, respectively for CG and ExG, a total weight loss of 37.8±9.3% and 38.4±10.3%, a body fat reduction of 60.4±13.7% and 61.9±15.2% and fat-free mass loss of 16.6±5.4% and 15.1±7.9%. Conclusion: This study shows that bariatric surgery candidates have low PA levels and rarely engage in MVPA. We found no additional effect to the standard of care treatment of a postoperative 12-week supervised exercise training program on weight loss trajectory, daily PA levels and sedentary behaviors. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Canadian Institutes of Health Research (CIHR)Institut Universitaire de Cardiologie et de Pneumologie de Québec - Université Laval (IUCPQ - UL)